Volume 6: Turbomachinery, Parts A, B, and C 2008
DOI: 10.1115/gt2008-51087
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study of Vane Clocking Effects on Embedded Compressor Stage Performance

Abstract: Previous research has shown that vane clocking, the circumferential indexing of adjacent vane rows with similar vane counts, can be an effective means to increase stage performance, reduce discrete frequency noise, and/or reduce the unsteady blade forces that can lead to high cycle fatigue. The objective of this research was to experimentally investigate the effects of vane clocking in an embedded compressor stage, focusing on stage performance. Experiments were performed in the intermediate-speed Purdue 3-Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Clocking configuration CL LE was the maximum efficiency configuration and CL MP was the worst efficiency configuration, similar to the turbine vane clocking results in the literature. Although details associated with the efficiency measurements can be found in [20], the focus of this paper is on using unsteady data to illuminate the flow physics responsible for this change in efficiency.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Clocking configuration CL LE was the maximum efficiency configuration and CL MP was the worst efficiency configuration, similar to the turbine vane clocking results in the literature. Although details associated with the efficiency measurements can be found in [20], the focus of this paper is on using unsteady data to illuminate the flow physics responsible for this change in efficiency.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…For example, Gundy-Burlet et al 19 and Dorney et al 17 concluded that the optimal combination of high efficiency occurred when the upstream stator wake was convected along the pressure surface of the downstream stator. On the contrary, He et al, 20 Hongyan et al, 16 Key et al, 18 and Fruth et al 21 observed maximum efficiency when the first stage/rotor wakes impinge on the leading edges of the second-stage rotor/stator, respectively. Städing et al 15 found best performance when the upstream rotor or stator wakes propagate near mid-passage of the clocked blade row.…”
Section: Guide Vane Rotormentioning
confidence: 97%
“…That the relation of clocking position and efficiency has a sinusoidal shape with typical variations within the range of 0.2 up to 2.7%, [13][14][15] is nowadays commonly accepted. [16][17][18] However, controversial findings have been reported regarding the optimal impingement location of the upstream stator wake on the downstream stator vane to maximise efficiency. For example, Gundy-Burlet et al 19 and Dorney et al 17 concluded that the optimal combination of high efficiency occurred when the upstream stator wake was convected along the pressure surface of the downstream stator.…”
Section: Guide Vane Rotormentioning
confidence: 99%
“…This has been 2 International Journal of Rotating Machinery done to study vane clocking, the circumferential indexing of adjacent vane rows with similar vane counts. Researchers have shown that vane clocking can impact stage loss and efficiency by changing the amount of interaction the upstream vane wakes have with the downstream vane boundary layer [5][6][7][8]. In this research, clocking is used to isolate the flow field effects associated with the downstream vane potential field.…”
Section: Introductionmentioning
confidence: 99%